In Quest of a Shared Planet : Negotiating Climate from the Global South. - Khan, Naveeda (New York : Fordham University Press, 2023)
An eye-opening firsthand account of the negotiating rooms responsible for the direction of the most urgent issue of our time.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books